The Integration of Aswaja NU Values and Kohlberg's Theory as the Foundation of Early Childhood Moral Education in Indonesia: A Conceptual Study - Leksana, Dinar Mahdalena Leksana; Naqiyah, Najlatun; Khusumadewi, Ari; Kurniawan, Shopyan Jepri (Directorate of Research and Community Service, Universitas Negeri Yogyakarta, 2025)
This article synthesizes the theory of moral development according to Lawrence Kohlberg with the values of Aswaja NU and the practice of guidance-counseling (BK) as a conceptual model of early childhood moral education in Indonesia. The purpose of the paper is to formulate an integrative framework that combines moral rationality (Kohlberg) with the spiritual-cultural dimension of Aswaja NU through the medium of implementing BK services in PAUD and elementary schools. The method used is a systematic review based on PRISMA 2015–2025 on reputable databases, followed by screening, quality assessment, and content analysis with thematic coding of 35 journal articles and 5 relevant book chapters. The results show: (1) the child's preconventional stage becomes the foundation of moral reasoning that needs to be stimulated through social-reflective experiences; (2) Aswaja values (tawassuth, tawazun, tasamuh, i'tidal, amar ma'ruf nahi munkar, rahmah) complement the individualistic-secular bias in the Kohlberg framework; (3) classical, group, and individual BK services are effective in internalizing values through dialogue, example, habituation, and behavior reinforcement. Conclusion: Kohlberg-Aswaja-BK integration produces a holistic, contextual, and applicative